(3TQM QSGdI GdTeSs - (3CHh YHO Gddg eMeO Hf QjMji GdCehj GdbQjTi GdChRGYis; (3eMeO Hf Gejd Hf YHO Gddg Hf Gejd (B( (3GSO (B)(3GdJejej,J (B170 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf hYdeg GdHjGf CeG HYO aEfi deG QCjJ cJH GdeJbOejf ef GdMceGA hQCjJ cdGe GdeJCNQjf s
(3BNQgG (B:s
(3COQcgG heYQJgG ee dGjYQa eG NGQL GdOGQ acja jYQa eG OGNdgG hef dGjYQa GdESde acja jYQa GdeSei JeJ HMeO Gddg hYhfg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs